A Dog Wearing Shoes - Ko, Sangmi (New York : Schwartz & Wade Books, 2015)
Mini finds a dog in the park wearing shoes but no collar and begs to keep him, but soon she realizes that whoever put the shoes on him loves the dog, as well.
Accelerated Reader AR